(untitled) (Research, Society and Development, 2022)
Introduction: Covid-19 is a viral disease that has reached the entire world and has become a concern for the health of the population, due to the high rates of deaths. As in Brazil the states are divided by health regions, this study aimed to analyze the profile of Covid-19 deaths in the health regions of the state of Pará. Method: This is a descriptive, retrospective research with a quantitative approach, whose data were collected from the digital platform of the SESPA. The study population was all confirmed Covid-19 deaths registered in the health regions of the state of Pará. Results: 14,864 deaths were registered in the state of Pará by Covid-19, and of the 13 health regions, the one with the most deaths was Metropolitan I. In general, the most affected age group was between 60 and 80 years or more, and males had the highest death rate with 59.14%. Conclusion: It was observed that the regional of the state capital, the one that presented the most deaths in the period of 1 year, and men are the sex that died most from Covid-19.